2007
DOI: 10.1186/1472-6947-7-20
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' intentions and use of three patient decision aids

Abstract: Background: Decision aids are evidence based tools that assist patients in making informed values-based choices and supplement the patient-clinician interaction. While there is evidence to show that decision aids improve key indicators of patients' decision quality, relatively little is known about physicians' acceptance of decision aids or factors that influence their decision to use them. The purpose of this study was to describe physicians' perceptions of three decision aids, their expressed intent to use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 32 publications
4
70
0
3
Order By: Relevance
“…Booklets and decision aids to educate families and nurses [162,185,186] are also available. One is specific to decisions regarding intake problems [185].…”
Section: Toolsmentioning
confidence: 99%
“…Booklets and decision aids to educate families and nurses [162,185,186] are also available. One is specific to decisions regarding intake problems [185].…”
Section: Toolsmentioning
confidence: 99%
“…Results from the in-depth interviews further revealed a limited understanding about the content and utility of PtDAs, which might have contributed to a sense of ambivalence about using PtDAs in clinical practice. The reluctance of physicians in using PtDAs has been reported in other studies (23,26,27). For example, a survey of Canadian family physicians, respirologists, and geriatricians found that although more than 80% believed that PtDAs could prepare patients to make informed treatment decisions, only 54% indicated an intention to use a PtDA in their practice, and less than one-third followed through (23).…”
Section: Discussionmentioning
confidence: 92%
“…The reluctance of physicians in using PtDAs has been reported in other studies (23,26,27). For example, a survey of Canadian family physicians, respirologists, and geriatricians found that although more than 80% believed that PtDAs could prepare patients to make informed treatment decisions, only 54% indicated an intention to use a PtDA in their practice, and less than one-third followed through (23). Interestingly, a 2012 survey in the Oregon Rural Practice-Based Research Network (n 5 174) found that 91% of rural primary physicians had used a paper-based or online PtDA in their clinical practice (28).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite strong evidence for efficacy, these interventions are rarely disseminated. 71 Future research should include implementation science, with creative attention to communication technology and cost-effective dissemination.…”
Section: -31mentioning
confidence: 99%